Health and health care in developing countries: closing the gaps - Leonard, Kenneth L. (Henry Stewart Talks, 2019)
Health care: primary health care and its access, The know-do gap, The information gap, Habit formation, Passive and active states when acquiring habits, Technology and health care quality, Patients and providers dynamics